The BumbleBox: An open‐source platform for quantifying behaviour in bumblebee colonies - August Easton‐Calabria; James D. Crall (Ecological Solutions and Evidence)
Abstract Bumblebees (Apini: Bombus) are important pollinators globally and an emerging model system for studying the ecology and evolution of social behaviour and effects of environmental stressors on bees. Behavioural studies of bumblebees have conventionally relied on labour and time‐intensive manual observations. While recent years have seen rapid advances in automated behavioural tracking in social insects, these tracking technologies are often expensive and require extensive programming experience, limiting accessibility and widespread adoption. Here we introduce the BumbleBox, an open‐source system for the tagging, automated tracking and behavioural quantification of individual bumblebees that can be built using low‐cost consumer components, DIY fabrication (i.e. 3D‐printing and laser‐cutting) and printed ‘Augmented Reality University of Cordoba’ (ArUco) markers. We provide an integrated pipeline for data collection and analysis, including nest arena design, software for automated collection of video data and the quantification of individual behaviour. Practical implication: The BumbleBox system is designed to be (a) accessible, requiring no prior experience with programming or hardware design to operate; (b) scalable, allowing long‐term, automated tracking across many units in parallel at low cost; and (c) modular, allowing for flexible adoption to unique applications in bumblebees and other systems. We validate the use of this system in a widespread bumblebee species (B. impatiens) that is both commercially and ecologically important. Finally, we highlight widespread potential applications in quantifying behaviour and pollinator health in bumblebees and other social insects, including screening impacts of pesticides and other environmental stressors on social behaviour.